Development and validation of a model for the simulation of the air drying phenomena in pipelines. (1st January 2013) - Crivellini, Andrea; Giacchetta, Giancarlo; Marchetti, Barbara; Marchetti, Cecilia; Paciarotti, Claudia; Terenzi, Alessandro
The main aim of this research work consists in the development and validation of a model, based on a numerical method, and its relevant simulation software, to solve the differential equations governing the drying process of gas pipelines. The knowledge of this phenomenon represents the key factor for performing effective pre-commissioning activities in petrochemical industry; in order to avoid hydrate formation and pipe corrosion, it is in fact necessary to achieve an effective removal of all water prior the introduction of hydrocarbon gas. This is normally achieved by performing a bulk dewatering operation, followed by a drying operation which efficiency is dependent on the air flow rate, air pressure and temperature. In this paper, the model implemented in a finite volume-based simulation software, as well as the considerations that have been made for its development, is presented. Its predictions are compared with available air drying field data of two existing gas pipeline systems.